Surface‐Specific Functionalization of Nanoscale Metal–Organic Frameworks. Issue 49 (23rd October 2015) - Wang, Shunzhi; Morris, William; Liu, Yangyang; McGuirk, C. Michael; Zhou, Yu; Hupp, Joseph T.; Farha, Omar K.; Mirkin, Chad A.
Abstract: A method for modifying the external surfaces of a series of nanoscale metal–organic frameworks (MOFs) with 1, 2‐dioleoyl‐ sn ‐glycero‐3‐phosphate (DOPA) is presented. A series of zirconium‐based nanoMOFs of the same topology (UiO‐66, UiO‐67, and BUT‐30) were synthesized, isolated as aggregates, and then conjugated with DOPA to create stably dispersed colloids. BET surface area analysis revealed that these structures maintain their porosity after surface functionalization, providing evidence that DOPA functionalization only occurs on the external surface. Additionally, dye‐labeled ligand loading studies revealed that the density of DOPA on the surface of the nanoscale MOF correlates to the density of metal nodes on the surface of each MOF. Importantly, the surface modification strategy described will allow for the general and divergent synthesis and study of a wide variety of nanoscale MOFs as stable colloidal materials. Abstract : Zr‐based MOF nanoparticles densely surface‐modified with 1, 2‐dioleoyl‐ sn ‐glycero‐3‐phosphate (DOPA) showed dramatically altered colloidal properties. Post‐synthetic modifications can thus be used to modify nanoMOF surface chemistry by coordination to exposed metal‐containing units, while retaining crystallinity and permanent porosity.